From Migrants to Citizens : Membership in a Changing World - Aleinikoff, T. Alexander (Thomas Alexander), 1952-; Klusmeyer, Douglas B., 1957- (Book collections on Project MUSE., 2000)
Citizenship policies are changing rapidly in the face of global migration trends and the inevitable ethnic and racial diversity that follows. The debates are fierce. What should the requirements of citizenship be' How can multi-ethnic states forge a collective identity around a common set of values, beliefs and practices' What are appropriate criteria for admission and rights and duties of citizens' This book includes nine case studies that investigate immigration and citizenship in Australia, the Baltic States, Canada, the European Union, Israel, Mexico, Russia, South Africa and the United States. This complete collection of essays scrutinizes the concrete rules and policies by which states administer citizenship, and highlights similarities and differences in their policies. From Migrants to Citizens, the only comprehensive guide to citizenship policies in these liberal-democratic and emerging states, will be an invaluable reference for scholars in law, political science, and citizenship theory. Policymakers and government officials involved in managing citizenship policy in the United States and abroad will find this an excellent, accessible overview of the critical dilemmas that multi-ethnic societies face as a result of migration and global interdependencies at the end of the twentieth century.